Analisa Kapasitas Produksi Line Welding LDT Menggunakan Metode Rough Cut Capacity Planning pada PT. ABC - Edison, Fauzan Wijdan Hilmi; Winarno, Winarno; Nugraha, Billy (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT ABC is a limited liability company engaged in heavy automotive production that has many products such as medium trucks, small trucks, bus chassis, engines and other spare parts. In assembling a Light Duty Truck through several work stations and must go through production schedule planning to meet the requested production demand. In the case of the welding line, there is a mismatch in production results with the planned production results at the end of the production period not in accordance with the scheduling carried out. So it is necessary to analyze production capacity using the calculation of Rough Cut Capacity Planning, after the calculation it is found that there are still several work stations that experience a lack of production capacity of -849 hours and excess capacity for production throughout the 12-month period. This shows that the lack of efficiency of the available capacity at each station in the LDT welding line so that it cannot produce according to the planned production demand